Trade-offs between efficiency, equality and equity in restoration for flood protection. (21st December 2021) - Villarreal-Rosas, Jaramar; Vogl, Adrian L; Sonter, Laura J; Possingham, Hugh P; Rhodes, Jonathan R
Abstract: Conservation decision-makers and practitioners increasingly strive for efficient and equitable outcomes for people and nature. However, environmental management programs commonly benefit some groups of people more than others, and very little is known about how efforts to promote equality (i.e. even distributions) and equity (i.e. proportional distributions) trade-off against efficiency (i.e. total net outcome per dollar spent). Based on a case study in the Brigalow Belt Bioregion, Australia, we quantified trade-offs between equality, equity, and efficiency in planning for flood protection. We considered optimal restoration strategies that allocate a fixed budget (a) evenly among beneficiary sectors (i.e. seeking equality among urban residents, rural communities, and the food sector), (b) evenly among local government areas (LGAs) within the Brigalow Belt (i.e. seeking spatial equality), and (c) preferentially to areas of highest socioeconomic disadvantage (i.e. seeking equity). We assessed equality using the Gini coefficient, and equity using an index of socioeconomic disadvantage. At an AUD10M budget, evenly distributing the budget among beneficiary sectors was 80% less efficient than ignoring beneficiary groups, and did not improve equality in the distribution of flood protection among beneficiary sectors. Evenly distributing the budget among LGAs ensured restoration in four areas that were otherwise ignored, with a modest reduction in efficiency (12%–25%). Directing flood protection to areas of highest socioeconomic disadvantage did not result in additional reductions in efficiency, and captured areas of high disadvantage for the rural and urban sectors that were missed otherwise. We show here that different ways of targeting equity and equality lead to quite different trade-offs with efficiency. Our approach can be used to guide transparent negotiations between beneficiaries and other stakeholders involved in a planning process.